Cyclic polygonal designs with block size 3 and joint distance 3 - M. H. Tahir; Ijaz Iqbal; Jamal Abdul Nasir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
Polygonal designs, a class of partially balanced incomplete block designs with regular polygons, are useful in survey sampling in terms of balanced sampling plans excluding contiguous units (BSECs) and balanced sampling plans excluding adjacent units (BSAs) when neighboring units in a population provide similar information. In this paper, the method of cyclic shifts is used and cyclic polygonal designs (CPDs) are constructed with block size k = 3 and [lambda] = 1, 2, 3, 4, 6,12 for joint distance » = 3 and v 21, 22,K ,100 treatments
Keywords: 330; BIBD; cyclic BSA; cyclic polygonal design; cyclic shifts; distance between; the units; joint distance; PBIBD; polygonal design